Civil Law Aspects; What is The Responsibility of The Board or Directors in The Case of Bankruptcy - Julius Caesar T Simorangkir (LEGAL BRIEF, 2021)
The existence of a business entity in improving various economies of human life, as well as the state is indeed the most important aspect that must be developed to date, so the establishment of a limited liability company to provide more benefits in the world of national and international companies becomes a necessity that cannot be ignored. argue again for the continuation of human progress. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that a Limited Liability Company or what we often know as a PT, is a development of a business entity formed on the basis of providing initial capital consisting of several people in terms of technical implementation, the nature of the PT itself is already a legal entity and is formed with various advantages and conveniences for investors in investing their investment capital in a very broad scope, officially the Indonesian government issued a notice regarding the company contained in the Limited Liability Company Law which has been undergoing various reforms, as one of the government's efforts to improve the country's trade system so that it is of higher quality and able to provide various benefits and revenues for the Indonesian state.